Effectiveness of Urea Molasses Multi-Nutrient Block Based on Fermented Coffee Fruit Peel on the Blood Profile of Sheep Experiencing Stress during Transportation - Fahriza, Shari; Yunilas; Ma’ruf Tafsin (Talenta Publisher, 2024)
Transportation stress is influenced by trip duration, mileage, vehicle type, road conditions, loading and unloading, vehicle speed and environmental conditions. The provision of Urea Molasses Multi-Nutrient Block (UMMB) based on fermented coffee peel aims to overcome nutritional deficiencies and stress in livestock. This study was conducted experimentally with a non-factorial complete randomized design (RAL) with 4 treatments of A0 (without UMMB) as a control, A1 (UMMB based on fermented coffee peel 10%), A2 (UMMB based on fermented coffee peel 20%), A3 (UMMB based on fermented coffee peel 30%) and 4 replications. The parameters of the study were glucose levels, total protein and creatinine. The results showed that giving UMMB peel-based fermented coffee has a significant effect (P<0.05) on increasing glucose levels (16.03%), decreasing total protein levels (31.49%), and decreasing creatinine levels (2.71%). It can be concluded that giving UMMB based on fermented coffee peel up to 30% can overcome stress in sheep that experience transportation for 8 hours.